Strategies for the development of three dimensional scaffolds from piezoelectric poly(vinylidene fluoride). (15th February 2016) - Correia, D.M.; Ribeiro, C.; Sencadas, V.; Vikingsson, L.; Oliver Gasch, M.; Gómez Ribelles, J.L.; Botelho, G.; Lanceros-Méndez, S.
Abstract: Cell supports based on electroactive materials, that generate electrical signal variations as a response to mechanical deformations and vice-versa, are gaining increasing attention for tissue engineering applications. In particular, poly(vinylidene fluoride), PVDF, has been proven to be suitable for these applications in the form of films and two-dimensional membranes. In this work, several strategies have been implemented in order to develop PVDF three-dimensional scaffolds. Three processing methods, including solvent casting with particulate leaching and three-dimensional nylon, and freeze extraction with poly(vinyl alcohol) templates are presented in order to obtain three-dimensional scaffolds with different architectures and interconnected porosity. Further, it is shown that the scaffolds are in the electroactive β-phase and show a crystallinity degree of 45%. Finally, quasi-static mechanical measurements showed that an increase of the porous size within the scaffold leads to a tensile strengths and the Young's modulus decrease, allowing tuning scaffold properties for specific tissues. Graphical abstract: Highlights: Three dimensional scaffolds based on electroactive PVDF have been fabricated. Three processing methods, including solvent casting and freeze extraction have been used. Different architectures and interconnected porosity have been achieved. The scaffolds are in the electroactive β-phase and show a degree of crystallinity of 45%. The scaffolds show suitable properties for novel tissue engineering applications.